Unusually Low Heat of Adsorption of CO2 on AlPO and SAPO Molecular Sieves - Pérez-Botella, Eduardo; Martínez-Franco, Raquel; González-Camuñas, Nuria; Cantín, Ángel; Palomino, Miguel; Moliner, Manuel; Valencia, Susana; Rey, Fernando (Frontiers in Chemistry, 2020)
The capture of CO2 from post-combustion streams or from other mixtures, such as natural gas, is an effective way of reducing CO2 emissions, which contribute to the greenhouse effect in the atmosphere. One of the developing technologies for this purpose is physisorption on selective solid adsorbents. The ideal adsorbents are selective towards CO2, have a large working adsorption capacity at atmospheric pressure and are easily regenerated, resulting in high working capacity. Therefore, adsorbents combining molecular sieving properties and low heats of adsorption of CO2 are of clear interest as they will provide high selectivities and regenerabilities in CO2 separation process. Here we report that some aluminophosphate (AlPO) and silicoaluminophosphate (SAPO) materials with LTA, CHA and AFI structures present lower heats of adsorption of CO2 (13 – 25 kJ/mol) than their structurally analogous zeolites at comparable framework charges. In some cases, their heats of adsorption are even lower than those of pure silica composition (20 – 25 kJ/mol). This could mean a great improvement in the regeneration process compared to the most frequently used zeolitic adsorbents for this application while maintaining most of their adsorption capacity, if materials with the right stability and pore size and topology are found.